Salt Solution Treatments Trigger Antioxidant Defense Response against Gray Mold Disease in Table Grapes - Youssef, Khamis (J Fungi (Basel), 2020)
To obtain a clear understanding of the mode of action of potassium bicarbonate (PB), sodium silicate (SSi) and calcium chelate (CCh) solutions (1%) in inducing resistance to gray mold disease in table grapes, enzymatic and nonenzymatic investigations were carried out. In particular, changes in the activity of the enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX) and peroxidase (POD), total phenolic content and total flavonoid content were studied. As indirect action, PB, SSi and CCh reduced the incidence of gray mold by 43%, 50% and 41%, respectively. The highest activity of SOD was detected at 48 h in SSi-treated tissue, PB-treated tissue and CCh-treated tissue, and it was 1.7-, 1.4- and 1.2-fold higher, respectively, compared to the control. The APX activity was significantly higher in SSi-treated tissue than in the control at 24, 48 and 72 h and showed an increase in activity 2-fold for all times. Additionally, PB, SSi and CCh increased the activity of POD by 1.4-, 1.2- and 2.7-fold at 48 h posttreatment, respectively. The results showed that CCh was the most pronounced salt to increase both total phenol and flavonoid contents by 1.3 and 2.1, respectively. Additionally, the three tested salts induced an increase in total phenols and total flavonoids at 48 h posttreatment. The obtained result is one more movement towards an overall understanding of the mechanism by which salt solutions act as antimicrobial agents against gray mold of table grapes.